Charakterystyka wybranych cech somatycznych oraz sposobu odżywiania studentów i studentek Uniwersytetu Zielonogórskiego w aspekcie ryzyka rozwoju chorób cywilizacyjnych = Description of selected somatic features and diet among students of the University of Zielona Góra in relation to the development of civilisation diseases - Jasik-Pyzdrowska, Justyna; Bonikowska, Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to determine the level of development of selected somatic features and to describe the typology of body build of students at the University of Zielona Góra. The presented typological and somatic characteristics were assessed in relation to health cho-ices regarding students' diet. The anthropometric measurements involved 882 students (565 women and 317 men). A diagnostic survey (by means of the questionnaire method used to evaluate students' particular health behaviors) was carried out among 500 students.
Keywords: choroby cywilizacyjne; otyłość; wskaźniki proporcji ciała; civilization diseases; obesity; body proportions